THE DETERMINANTS OF ROA (RETURN ON ASSETS) OF FULL-FLEDGED ISLAMIC BANKS IN INDONESIA - Shinta Amalina Hazrati Havidz; Chandra Setiawan (Universitas Mercu Buana, 2015)
Abstract.The main objectives of this research is to examine the determinants of ROA (Return on Assets) of Full-fledged Islamic banks in Indonesia in the period of January 2008 – December 2011 using monthly-published report data of Central Bank (Bank Indonesia) with 3 full-fledged Islamic banks in Indonesia as the samples of the research. Panel Least Square is applied as the research method where those data had been tested with the classical assumption test, such as: normality, autocorrelation, multicollinearity and heteroscedasticity tests. However, the data could not fulfill the normality test, while the remaining assumption tests is fulfilled. The findings reveal that Financing to Deposit Ratio (FDR), Debt to Total Assets Ratio, Capital Adequacy Ratio (CAR), Size and Operational Efficiency Ratio (OER) have significant effect simultaneously towards ROA. Partially, FDR, DTAR, and CAR have positive effect and significant towards ROA, while size and OER have negative effect and significant towards ROA.Size is the highest coefficient among the determinant variables, while FDR is the weakest coefficient that effect ROA in the full-fledged Islamic banks in Indonesia.Keywords: return on assets , Financing to Deposit Ratio, Debt to Total Assets Ratio, Capital Adequacy Ratio, Size, Operational Efficiency Ratio